LAGOS STATE’S USE OF MOTORCYCLES FOR TRANSPORTATION: SWEET NIGHTMARE - GIWA M.O.; .R.O, Olorunnimbe; A.H, Fagbenro (IJRDO - Journal of Social Science and Humanities Research, 2023)
In Lagos, the use of motorcycles as a mode of transportation has gained popularity. It is frequently used and favored by residents due to its capacity to help people save time, get rid of traffic jams and terrible roads, and attend to urgent needs. Despite its clear advantages, this means of transport has been blamed for an increase in ridership-related crimes. Therefore, the study looked at how Lagos perceived crime among Okada riders. A sample size of 400 respondents was used for the study, and data were gathered using methodological triangulation (the use of both quantitative and qualitative methodologies) (375 randomly selected respondents for the survey and 25 purposefully selected respondents for the qualitative data). The study also revealed that, although it is popularly believed that Okada riders commit crimes, the majority of people hold the opinion that not all Okada riders are hazardous. Findings demonstrate the seriousness of the effects Okada crimes have on their victims, including the loss of lives, destruction of property, physical harm, psychological distress, and stress. The study also finds that there is a strong correlation between the perception of crimes and the usage of Okada and that women are more vulnerable to Okada crimes than men because they are frequently viewed as weaker and simpler targets.